Analyzing homoeolog expression provides insights into the rediploidization event in gynogenetic hybrids of Carassius auratus red var. × Cyprinus carpio. Issue 1 (December 2017) - Ren, Li; Cui, Jialin; Wang, Jing; Tan, Hui; Li, Wuhui; Tang, Chenchen; Qin, Qinbo; Liu, Shaojun
Abstract Rediploidization is considered to be a part of the evolutionary history of allotetraploids, and resulted in the emergence of novel epigenetic regulatory activities. To study the changing patterns of gene expression following the reduction of a genome by 50%, we used RNA-seq and quantitative real-time PCR (qPCR) to investigate total gene expression and homoeolog expression in three hybrids of aC .auratus red var. (2n = 100, ♀) (R) andC .carpio (2n = 100, ♂) (C) (i.e., F1, F18, and G4 ) and their original parents. A comparison of homoeolog expression between G4 and F18 identified 7 genes (0.22%) that exhibited novel R/C homoeolog expression patterns in G4, while 4 genes (0.12%) were affected by R/C homoeolog silencing. We determined the direction and extent of the homoeolog expression bias (HEB). The C-HEB genes (i.e., nrp1a andigf1) and R-HEB genes (i.e., fgf23 andesm1 ) provided insights into the effects of the dominance of one parental homoeolog expression on growth regulation. This dominance may contribute to the rapid growth of G4 fish. Our findings may be relevant for clarifying the relationship between growth heterosis and differences in homoeolog expression patterns.